The Mediating Effect of Leader Accountability on the Relationship between Transcendental Leadership of School Heads and Teacher Self-Efficacy - Cindy Gonzalez; Ester Jean U. Pelayo (International Journal of Educational Administration, Management, and Leadership, 2022)
This study investigated the mediating influence of leader accountability on the relationship between transcendental leadership of school heads and teacher self-efficacy in public secondary schools in two municipalities of Davao Oriental. (Failure of teachers to maintain and improve their own performance in the classroom can have a significant impact on the students' learning. The ineffectiveness of teachers has an influence on the entire educational system. Teachers that are inept will have a detrimental influence on student learning results. Self-efficacy relates to one's belief in one's own skills and inefficiencies, which may lead to a number of psychological issues such as low confidence and low self-esteem). A stratified random sample approach was adopted, with 300 teachers serving as respondents. The findings of a non-experimental quantitative mediation study using medgraph, a validated questionnaire, mean, regression procedures, and Pearson r revealed substantial correlations between school leaders' transcendental leadership, teacher self-efficacy, and leader accountability. The mediating influence of leader accountability on the relationship between school leaders' transcendental leadership and teacher self-efficacy was partial. As a result, one of the ways that transcendental leadership of school heads may influence teacher self-efficacy is through leader accountability. However, this does not fully explain the relationship between the two variables.